Tracking labels for occurrences of alleged child abuse from police interviews to trials - Danby, Meaghan C. (Legal and criminological psychology, 2019)
Purpose. Labelling (i.e., naming) individual occurrences of repeated abuse allegations with explicit and consistent terms may improve children's reporting of these offences. The aim of the present study was to track labels for occurrences of alleged child sexual abuse from the police interview to court proceedings. Methods. We examined the labels used in the police interviews and trials of 23 child complainants (5–15 years old at interview). The initiator of each label (child, interviewer, lawyer, or judge), stage of the process in which the label was generated, and the type of information used to label specific occurrences of abuse were recorded. Any subsequent reuse or replacement of the labels was also recorded. Results. Most labels were created by police interviewers. Few children generated labels. Most occurrences of abuse were labelled early in the legal process; 82% were first labelled either in the police interview or in the prosecution's opening statement. The labels were frequently replaced with alternate terms, with an average of three different labels for the same incident. After original labels were established for occurrences, they were just as likely to be replaced as they were to be reused. The most frequently observed label replacement was by defence lawyers during cross-examination. Conclusions. Labels were used inconsistently throughout the police interview and trial. To give children the best chance of describing specific occurrences of abuse during legal proceedings, labels should be created from children's words wherever possible and used consistently thereafter by all justice professionals.